1979
DOI: 10.1111/j.1600-0536.1979.tb04912.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in rabbits after application of medicaments and cosmetic bases

Abstract: A staged histological study of skin changes induced in rabbits by daily application of five bases used for topical medicaments and cosmetics, namely glycols, petrolatum, Modulan, Acetulan and Amerchol L 101, over periods of 100 days, is reported. Sections obtained every 10 days were examined for changes in the epithelium, in the character of the dermal infiltrate and in the superficial collagen fibers. Glycols showed no particular effects on the skin; petrolatum produced acanthosis and vacuolization in the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Several studies of the histology of experimentally induced cumulative irritation have been reported (7–10). In these studies, medicaments and cosmetic bases showed different grades of irritancy, however, it was not clearly described whether differences exist according to the chemical nature of irritants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of the histology of experimentally induced cumulative irritation have been reported (7–10). In these studies, medicaments and cosmetic bases showed different grades of irritancy, however, it was not clearly described whether differences exist according to the chemical nature of irritants.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on dermal irritation to petrolatum in laboratory animals. In addition to the two previous publications (Budhiraja et al ., ; Rantuccio et al ., ), acanthosis in the skin of guinea pigs has been described (Wollmann et al ., ). As indicated previously, dermal irritation (either clinically or microscopically) was not observed in Wistar‐Han rats, CD1 or C57Bl/6J mice or Göttingen minipigs treated topically with white petrolatum.…”
Section: Discussionmentioning
confidence: 95%
“…In the other earlier study (Budhiraja et al ., ), petrolatum (white and yellow) was applied for 10 days and skin for histological examination was obtained on Study Day 11 and Study Day 15. Similar to the findings observed in this study, erythema and edema was noted clinically, with thickening of the epidermis, hyperkeratosis and marked cellular infiltration of the dermis (Rantuccio et al ., ). Budhiraja et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment of the SC with cationic surfactants can markedly increase the transport of hydrophilic substances. 13,14) Application of even diluted solutions of cationic surfactants to the skin changes the structure of the lipid bilayers in the skin.…”
Section: Back Diffusion Of Glucose Enhanced By Surfactant Pretreatmentsmentioning
confidence: 99%